1998
DOI: 10.1073/pnas.95.4.1764
|View full text |Cite
|
Sign up to set email alerts
|

Antisense inhibition of the PTI-1 oncogene reverses cancer phenotypes

Abstract: The genetic alterations and molecular events mediating human prostate cancer development and progression remain to be defined. Rapid expression cloning and differential RNA display detect a putative oncogene, prostate tumor-inducing gene 1 (PTI-1), that is differentially expressed in human prostate (as well as breast, colon, and small cell lung) cancer cell lines, patient-derived prostate carcinomas, and blood from patients with metastatic prostate cancer. PTI-1 consists of a unique 5 untranslated region (5 UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…As PTI-1 is unable to undergo the GTP-binding-induced conformation change proposed for intact eEF1A, we examined whether it may function as a constitutive activator of SK1. Furthermore, although the origin of PTI-1 has been the subject of some debate (Mansilla et al, 2005), a number of studies have reported its expression specifically in tumour cells and tissues (Gopalkrishnan et al, 1999), and demonstrated its ability to induce neoplastic transformation (Su et al, 1998). The mechanism whereby PTI-1 exerts its oncogenic effects, however, has not been established.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As PTI-1 is unable to undergo the GTP-binding-induced conformation change proposed for intact eEF1A, we examined whether it may function as a constitutive activator of SK1. Furthermore, although the origin of PTI-1 has been the subject of some debate (Mansilla et al, 2005), a number of studies have reported its expression specifically in tumour cells and tissues (Gopalkrishnan et al, 1999), and demonstrated its ability to induce neoplastic transformation (Su et al, 1998). The mechanism whereby PTI-1 exerts its oncogenic effects, however, has not been established.…”
Section: Resultsmentioning
confidence: 99%
“…Ectoptic expression of PTI-1 or overexpression of SK1 have both been shown to induce neoplastic cell transformation (Su et al, 1998;Xia et al, 2000). Thus, we next examined the possible role of SK1 in PTI-1-induced oncogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Antisense-mediated blocking of PTI-1 inhibits tumorigenesis and results in the reversion of tumor cells to a normal cellular phenotype. 32 As it bears a strong sequence similarity to eEF1A1, eEF1A2 is also involved in cancer. The amplification of the eEF1A2 gene, which maps to 20q13, occurs in 20-30% of ovarian cancer cases 18 and two-thirds of breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thymidine uptake for DNA synthesis was determined by the measurement of the rate of [ 3 H]dThd incorporation into trichloroacetic acid-precipitable material. 4 Colony formation in soft agar was performed as described previously. 4 For cytotoxicity, a 50% inhibition of cell growth (IC 50 ) of these cells for the drugs was determined by a dye reduction assay using 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) (Sigma, St. Louis, Mo).…”
Section: Cellsmentioning
confidence: 99%
“…Antisense therapeutics, which exploit the high degree of specificity offered by the base pair recognition of genetic information 1 may have promising therapeutic value in cancers, including colon cancers, because of their specificity in targeting gene products with minimal side effects. This therapy has the ability to suppress neoplastic phenotypes in cancer cells [2][3][4] and bring about an inhibition of chimeric bcr-abl gene expression in Philadelphia chromosome-positive cells in chronic myeloid leukemia, such as a reduction in bcr-abl mRNA at p210bcr-abl levels. 5,6 Successful results in antisense technology, however, have been demonstrated only in in vitro or culture systems.…”
mentioning
confidence: 99%